Nearest neighbor analysis of the spread of tuberculosis in Padang - Sidiq, Rapitos; Dewata, Indang; Heldi, Heldi; Hayati, Neni Fitra (International Journal of Public Health Science (IJPHS), 2024)
The rate of Tuberculosis (TB) cases in Padang has never dropped appreciably from year to year. Cases continue to be reported in all working regions of Puskesmas (primary healthcare center) although the precise transmission site is unknown. This study aims to determine the distribution pattern of TB sufferers in 4 Health Center working areas with the highest incidence using nearest neighbor analysis. This quantitative descriptive study used secondary data from the Padang Health Office and 4 working regions of primary healthcare centers from 2022 to March 2023, totaling 938 cases. The evidence is supported by actual observations of the physical conditions of the environment where TB patients live. The investigation of the ArcGIS program discovered that of the 4 working regions of primary healthcare centers. Mapping revealed that all locations showed a cluster pattern of TB transmission. It is hoped that these findings will be useful for health institutions in determining interventions so they can break the chain of TB transmission.